L’utilisation Des Structures De Soins Dans La Région Du Logone Occidental Au Sud Du Tchad, Un Défi Pour La Gouvernance En Santé - Sabine, Djimouko; Robert, Madjigoto; H.B., Nguendo-Yongsi; Michel, Tchotsoua (European Scientific Journal, ESJ, 2016)
Background: Health situation in Chad, particularly in the Western Logone is characterized by a general high morbidity, a difficult access to healthcare structures, and by a plurality of healthcare provision. In the evnt of illnesses, very few patients (18%) resort to modern healthcare. Objective: This study aims at adressing the link between the provision of healthcare system, geographical accessibility and patients therapeutic behaviors . Methods: We have resorted to methodology usually used in in geography that is review literature, surveys and interviews. Over the 429 investigated households, a response rate of 99.9% was obtained.. Levels of analyses include both descriptive and explanatory analyses. Results: 96% of the investigated individuals live close to a health center (0 to 10 kms) is. Conversely, 75% are attending healthcare centers located beyond 10 kms. In the event of illnesses, about 82% of patients resort firstly to traditional care